METODE CERAMAH DAPAT MEMPENGARUHI PENGETAHUAN SISWI SD DALAM MENGHADAPI MENARCHE - Laily Mualifah (Jurnal Kesehatan Karya Husada, 2015)
Background: Menarche and menstruation is a physiological process that can cause physical discomfort, emotional and anxiety. SDN in Districts Nanggulan there were 6 from 10 pra puberty are not yet menarche say not know about menarche and menstruation and not knowing what to do when menstruation occurs. This happens because there is no health education about menstruation health in the scope of elementary school.Objective: To find the influence of health education with lecture method to the knowledge to face of menarche.Materials and Methods: This study is quasy-experiment with approaches pre test-post test group design. Subjects were 5th and 6th grade students of elementary school at Nanggulan Kulon Progo with as many as 56 who met the inclusion criteria. The instrument used questionnaire modification from Fauziah (2005) and BKKBN (2009). The sampling technique purposive sampling. Statistical test using Wilcoxon test.Results: Scores of knowledge before and after treatment there were significant differences in lectures with the p=0,00 (p <0.05).Conclusion: Health education with lecture method in increasing knowledge in the pra-puberty facing menarche.